Use of supplements by young elite Japanese athletes participating in the 2010 Youth Olympic Games in Singapore - Sato, A.; Kamei, A.; Kamihigashi, E.; Dohi, M.; Komatsu, Y.; Akama, T.; Kawahara, T. (Clinical Journal of Sport Medicine, 2012)
Objective: To investigate the prevalence of supplement use among young elite Japanese athletes.